Integrative transcriptome analysis reveals alternative polyadenylation potentially contributes to GCRV early infection - Tan, Sheng; Zhang, Jie; Peng, Yonglin; Du, Wenfei; Yan, Jingxuan; Fang, Qin (Frontiers in Microbiology, 2023)
Introduction Grass carp reovirus (GCRV), a member of the Aquareovirus genus in the Reoviridae family, is considered to be the most pathogenic aquareovirus. Productive viral infection requires extensive interactions between viruses and host cells. However, the molecular mechanisms underlying GCRV early infection remains elusive. Methods In this study we performed transcriptome and DNA methylome analyses with Ctenopharyngodon idellus kidney (CIK) cells infected with GCRV at 0, 4, and 8 h post infection (hpi), respectively. Results We found that at early infection stage the differentially expressed genes related to defense response and immune response in CIK cells are activated. Although DNA methylation pattern of CIK cells 8 hpi is similar to mock-infected cells, we identified a considerable number of genes that selectively utilize alternative polyadenylation sites. Particularly, we found that biological processes of cytoskeleton organization and regulation of microtubule polymerization are statistically enriched in the genes with altered 3’UTRs. Discussion Our results suggest that alternative polyadenylation potentially contributes to GCRV early infection.